Anomalous Nernst effect and three-dimensional temperature gradients in magnetic tunnel junctions. Issue 1 (December 2018) - Martens, Ulrike; Huebner, Torsten; Ulrichs, Henning; Reimer, Oliver; Kuschel, Timo; Tamming, Ronnie; Chang, Chia-Lin; Tobey, Raanan; Thomas, Andy; Münzenberg, Markus; Walowski, Jakob
Abstract Localized laser heating creates temperature gradients in all directions leading to three-dimensional electron flux in metallic materials. Temperature gradients in combination with material magnetization generate thermomagnetic voltages. The interplay between these temperature gradients and the magnetization along with their control enable to manipulate the generated voltages in magnetic nanodevices. We present a highly sensitive method to identify the anomalous Nernst effect generated on the nanometer length scale by micrometer-sized temperature gradients in magnetic tunnel junctions with CoFeB electrodes and a MgO tunnel barrier systematically extracted by analyzing the influence of in-plane temperature gradients on the tunnel magneto-Seebeck effect. This method yields an anomalous Nernst effect coefficient ofK N  ≈ 1.6 × 10−8  V T−1  K−1 for CoFeB. Generally, such investigations are motivated by utilizing otherwise wasted heat in magnetic memory devices for read/write operations. The additionally generated anomalous Nernst effect offers a functionality expansion, opening new application fields such as direction-dependent temperature sensing with downscaling potential. Understanding nanoscale temperature gradients in magnetic materials and how it affects their properties can help widen their potential applications. The authors analyze the anomalous Nernst effect in magnetic tunnel junctions and report how temperature gradients influence the thermomagnetic properties in three dimensions.